Molecular simulation of protein-ligand complexes - Guest, Ellen (2022)
Computational methods provide important contributions to modern drug discovery projects. In this thesis, we discuss the insights into protein-ligand interactions afforded by methods such as molecular docking, molecular dynamics (MD) and alchemical free energy calculations, which expedite the process of lead compound design and optimisation. These methods are applied to two case studies of biomolecular systems of therapeutic interest. The targets of the studies are the integrin αvβ6 and the bromodomain-containing protein 4 (BRD4). As the accuracy of molecular mechanics based methods relies on the quality of the force field in which the potential energy is calculated from, we focus on developing force field parameters for a series of small molecule inhibitors of αvβ6. Parameters are then applied to MD and relative free energy perturbation (FEP) simulations. MD simulations highlight the importance of hydrogen bonds, metal chelate interactions and cation-